2023
DOI: 10.1093/evolut/qpad061
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the fraction of new mutations that are recessive lethal

Abstract: The presence and impact of recessive lethal mutations has been widely documented in diploid outcrossing species. However, precise estimates of the proportion of new mutations that are recessive lethal remain limited. Here, we evaluate the performance of Fit∂a∂i, a commonly-used method for inferring the distribution of fitness effects (DFE), in the presence of lethal mutations. Using simulations, we demonstrate that in both additive and recessive cases, inference of the deleterious non-lethal portion of the DFE… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 60 publications
3
5
0
Order By: Relevance
“…3), consistent with previous work demonstrating that such mutations are likely to be highly recessive [14,15,17,25,37,38]. For instance, the impacts of recessive lethal mutations in humans are well documented [37, 43,44], though evidence from Drosophila suggests that such lethal mutations may in fact have a small fitness consequence in the heterozygote state [17], consistent with our findings (Figs. 2 & 3) Dominance is an essential determinant of the influence of demography on patterns of deleterious variation [1,2,4,5].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…3), consistent with previous work demonstrating that such mutations are likely to be highly recessive [14,15,17,25,37,38]. For instance, the impacts of recessive lethal mutations in humans are well documented [37, 43,44], though evidence from Drosophila suggests that such lethal mutations may in fact have a small fitness consequence in the heterozygote state [17], consistent with our findings (Figs. 2 & 3) Dominance is an essential determinant of the influence of demography on patterns of deleterious variation [1,2,4,5].…”
Section: Discussionsupporting
confidence: 93%
“…However, we note that a major limitation of our study is that we are unable to finely estimate selection and dominance parameters for strongly deleterious mutations, which as defined here encompass a wide range of |s| from 0.01 to 1. This limitation is due to SFS-based methods being underpowered for estimating the strongly deleterious tail of the DFE [44], due to the fact that such mutations tend not to be segregating in genetic variation datasets [48][49][50]. Thus, an important area for future work is to further refine selection and dominance parameters for strongly deleterious mutations and determine whether dominance parameters may differ between strongly deleterious mutations (|s| on the order of ~0.01) and lethal mutations (|s|=1).…”
Section: Discussionmentioning
confidence: 99%
“…Most DFE inference methods assume that new mutations are semidominant and thus provide estimates of the joint distribution of the selection and dominance coefficients, “ s d ℎ”. A recent study by Wade et al . (2023) suggests that, if there are recessive lethal mutations, current DFE inference approaches can lead to underestimating the true proportion of strongly deleterious mutations, as more strongly deleterious mutations are likely to persist in the population if they are recessive.…”
Section: Resultsmentioning
confidence: 96%
“…We only modeled two very simple DFEs for synonymous mutations: a uniform DFE across all synonymous mutations and a partial DFE, where 22% of synonymous mutations have the same selection coefficient and the rest are neutral. While it has been established that the DFE of non-synonymous sites is well represented by a gamma distribution (Eyre-Walker et al 2007; Kim et al 2017; Wade et al 2023), the shape of the DFE of synonymous sites has not been well characterized. However, some studies have shown evidence that at least a portion of synonymous sites are under moderate ( Ns >1) to strong ( Ns >10) selection in both Drosophila (Lawrie et al 2013) and humans (Keightley and Halligan, 2011).…”
Section: Discussionmentioning
confidence: 99%